(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
The genus Malva L., popularly known as mallow, grows spontaneously in almost all of Europe and the Mediterranean region. This genus is morphologically very diverse and its species are used in the treatment of respiratory, urinary, and digestive problems, but some species are hardly distinguishable based on morphological features. We, therefore, performed a molecular data analysis for this genus. Amplification of genomic DNA of 90 randomly selected samples of six species of Malva using 5 primers produced 83 bands, of which 77 were found to be polymorphic (90.99%). The high average PIC and MI values revealed the high capacity of ISSR primers to detect polymorphic loci among Malva species. The genetic similarities of the six collections were estimated from 0.73 to 0.90. ISSR analysis revealed that Malva parviflora and M. vericillata had the lowest similarity whereas, M. neglecta and M. sylvestris had the highest similarity. Bangladesh J. Plant Taxon. 29(2): 193-202, 2022 (December)